2019
DOI: 10.1177/1687814019826644
|View full text |Cite
|
Sign up to set email alerts
|

A novel fault diagnosis approach of a mechanical system based on meta-action unit

Abstract: When a mechanical system fails, the most important thing is to find out the fault location and causes quickly and accurately. Based on the meta-action unit, this article proposes a comprehensive, qualitative, and quantitative fault diagnosis method composed of fault tree analysis and evidential network to analyze faults of the mechanical system. First, we expand the function-motion-action decomposition method, revise the definitions of meta-action and meta-action unit derived from the function-motion-action de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Then, Li et al [28] and Ran et al [29] presented the definition of the meta-action: the action that has the relatively independent controllable and analyzable structure, has the ability to achieve a certain motion target or to achieve a certain goal, and cannot be decomposed into other actions. Zhang et al [30] revised the definition of meta-action as the elementary mode of motion that can transmit the movement and momentum in a mechanical system. They limited the application of meta-action in mechanical system and defined meta-action unit (MU).…”
Section: Meta-actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, Li et al [28] and Ran et al [29] presented the definition of the meta-action: the action that has the relatively independent controllable and analyzable structure, has the ability to achieve a certain motion target or to achieve a certain goal, and cannot be decomposed into other actions. Zhang et al [30] revised the definition of meta-action as the elementary mode of motion that can transmit the movement and momentum in a mechanical system. They limited the application of meta-action in mechanical system and defined meta-action unit (MU).…”
Section: Meta-actionmentioning
confidence: 99%
“…Thus, the mechanical system can be decomposed into a series of meta-action units (MUs) in structure. According to [30], a meta-action unit in general consists of five elements: input part, middle part, strut member, fastener and output part. The input part and output part are the key elements for MU.…”
Section: Meta-actionmentioning
confidence: 99%
“…At present, the research on meta‐action unit has been relatively mature, and some achievements have been achieved, such as Refs. (25–30). In order to eliminate the early failure of electromechanical product as much as possible before it leaves the factory, it is necessary to establish a reasonable failure elimination system.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can be concluded that the failure of electromechanical product's function and performance is ultimately caused by the failure of mechanical parts' motion state. 1,[13][14][15] All the parts used to realize a meta-action can be treated as a whole (meta-action unit) according to the concept of meta-action unit, which can simplify the analysis process and refine the analysis results. 11 The failure of meta-action is the most direct manifestation of electromechanical product failure.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-action and meta-action unit were first put forward by our team, and some achievements have been achieved, such as literature. 1,[13][14][15] All the parts used to realize a meta-action can be treated as a whole (meta-action unit) according to the concept of meta-action unit, which can simplify the analysis process and refine the analysis results. Reasonable metaaction decomposition method and meta-action unit separation criterion are beneficial to the subsequent analysis of quality characteristics based on them.…”
Section: Introductionmentioning
confidence: 99%